Potential Of Stichopus horrens And Stichopus vastus Extracts As Anticancer And Wound Healing Agents: Effects On Breast Cancer And Fibroblast Cell Lines - Azemi, Nurul Adila (2014)

(untitled)
The commercial exploitation of sea cucumbers biomass due to healthy lifestyle are gaining much recognition among consumers, pharmaceutical industries and researchers. In peninsular Malaysia, the medicinal uses of sea cucumbers locally known as ‘gamat’ (Sea cucumbers of the Stichopodidae family), have been exploited. Eksploitasi komersial ke atas timun laut disebabkan oleh peningkatan amalan gaya hidup sihat di kalangan masyarakat telah banyak mendapat pengiktirafan di kalangan pengguna, industri farmaseutikal dan para penyelidik. Di semenanjung Malaysia, kegunaan timun laut tempatan yang juga dikenali sebagai gamat (Stichopodidae) dalam perubatan telah lama dieksplotasi.